Perceived social support, coping capability and gender differences among young adults - Tam, Cai Lian *; Lim, Swee Geok (Sunway University College, 2009)
Perceived social support and coping capabilities are important predictors which give an insight into how different individuals deal with stressful situations in life. Studies have reported that different genders address the variables differently. Thus, this research aims to find out how well perceived social support predicts the coping capability of early adulthood. 300 respondents were tested with 2 scales: Perceived Social Support Scale which consists of Friend scale (PSS-Fr), Family scale (PSS-Fa), and Adolescent Coping Orientation for Problem Experiences (A-COPE). The age range of respondents was from 16 to 26 years old. Questionnaires were distributed to several secondary schools, colleges, and university students within the Klang Valley, Malaysia. The result indicated that there was a significant positive relationship between perceived social support and coping capability. In addition, perceived social support from family played a more important role in determining coping capability. Furthermore, it was found that perceived social support from females differed significantly from males in the analysis of t test. In addition, results also revealed that there were significant gender differences for young adult?s coping capability whereby females were generally better coping had capability, as compared with males.